The Prevalence of Suicidal Ideation after the Earthquake: A Systematic Review and Meta-Analysis - Katayoun JAHANGIRI; Kosar YOUSEFI; Aliashraf MOZAFARI; Ali SAHEBI (Tehran University of Medical Sciences, 2020)
Background: Disasters have many health consequences such as suicide ideation as one of the relatively common psychological consequences after natural disasters, especially earthquakes. This study aimed to determine the prevalence of post-earthquake suicidal ideation in affected people. Methods: Related keywords of this systematic review and meta-analysis in English and their Persian equivalents were searched in the data resources including Google Scholar, SID, Magiran, Scopus, PubMed, and Web of Science from Jan 2014 to May 2019. The STROBE checklist was used to evaluate the quality of the articles. The I2 index was used to determine the heterogeneity and the random-effects model was used in meta-analysis. Statistical analysis was conducted in the STATA software version 14. Results: Overall, 14347 subjects including 6662 males and 7715 females with the mean age of 23.88 ± 15.81yr old were assessed. The prevalence of post-earthquake suicidal ideation was 20.34% (95% CI: 13.60-27.08, P<0.001, I2=99.1). The prevalence of suicidal ideation showed a decreasing trend based on the year of the study and the duration of post-earthquake follow-up. Conclusion: Although the prevalence of post-earthquake suicidal ideation showed a decreasing trend, the probability of incidence of these thoughts in the long-term is still noticeable. Therefore, implementing a surveillance system is recommended to monitor the mental health status of earthquakes survivors for the possibility of suicidal thoughts in the short and long term recovery phase.